Pengaruh Inflasi, Suku Bunga, dan Kurs USD Terhadap Indeks Kompas 100 - Rhesandyka Abdie Saputra; Imron Rosyadi (Cakrawala Repositori IMWI, 2023)
The capital market is an activity related to public offerings and securities trading, public companies that are correlated with securities. The capital market has an important role in the economy of a country. An index is used to measure the performance of stocks traded on the stock exchange. This study aims to measure the influence of macro factors in the form of inflation, interest rates and the USD exchange rate on the Kompas 100 index. This research uses secondary data from 2019 to 2021. The analytical method used is multiple regression analysis. The population of this study are all companies listed on the Indonesian Stock Exchange's Kompas 100 index for 2019-2021. The sample was selected using the purposive sampling method in order to obtain a sample of 36. The results showed that simultaneously inflation, interest rates, and the USD exchange rate had a significant effect on the Kompas 100 index. Partially, inflation had a negative and insignificant effect on the Kompas 100 index, interest rates had a positive effect. and significant to the Kompas 100 index, and the USD exchange rate has a negative and significant effect on the Kompas 100 index. The ability of investors to understand and predict future macroeconomic conditions greatly assists investors in making investment decisions.